The Inductive Software Engineering Manifesto: Principles for Industrial Data Mining - Menzies, Tim; Bird, Christian; Zimmermann, Thomas; Schulte, Wolfram; Kocaganeli, Ekrem; Zimmermann, Tom (Proceedings of the International Workshop on Machine Learning Technologies in Sofware Engineering, 2011)
The practices of industrial and academic data mining are very different. These differences have significant implications for (a) how we manage industrial data mining projects; (b) the direction of academic studies in data mining; and (c) training programs for engineers who seek to use data miners in an industrial setting.